Scientific mentoring in the system of continuous pedagogical education as a subject of research reflection - V. K. Shapovalov; I. F. Igropulo; A. I. Dunayenko (Вестник Северо-Кавказского федерального университета)
The announcement of 2023 as the Year of Teachers and Mentors actualizes the social and scientific significance of the study of mentoring in various fields of professional activity. The article is devoted to the analysis of the content and features of scientific mentoring in the system of continuous pedagogical education. The research is based on fundamental ideas and principles of a systematic approach, which provided a comprehensive analysis of scientific mentoring as a multidimensional holistic phenomenon. Research objectives include the analysis of scientific mentoring as an interdisciplinary scientific phenomenon; identification of the target and content-technological features of scientific mentoring in the system of continuing pedagogical education; substantiation of the multifunctionality of scientific mentoring in the system of continuous pedagogical education at the present stage of the development of the education sciences.The novelty of the obtained results lies in the identification and characterization of the target and content-technological features of scientific mentoring at various levels of the system of continuous pedagogical education; in proving the multifunctionality of scientific mentoring. The multifunctionality of scientific mentoring is manifested in the integrative interrelation of axiological, methodological, teaching, motivational, and communicative functions. The theoretical significance of the obtained results lies in the expansion of ideas about the features of scientific mentoring, systematization of data on educational and developmental potential of scientific mentoring in the system of continuous pedagogical education. The obtained results can find practical application in the organization of educational and research work with students of psychological and pedagogical specialization, with bachelor and master students of pedagogy studies, graduate students and teachers at various stages of their professional and career development in the field of scientific and pedagogical activity.